Effect Of Ambient Temperature On Diesel-Engine Combustion Characteristics Operating With Alcohol Fuel - Mohammad Akmal, Akashah; R., Mamat; Abdul Adam, Abdullah; A., Aziz; H. M., Yassin (Universiti Malaysia Pahang, 2015)
Biofuel is an alternative fuel source for diesel engines. Nowadays, biofuel attracts more interest due to the depletion of mineral petroleum resources. The aim of this paper is to study the effect of ambient temperature on the combustion and performance of a diesel engine when using ethanol and methanol as fuels. The one-dimensional numerical analysis uses the GT-Power software program to simulate a commercial four-cylinder diesel engine. The diesel engine was simulated in order to study the characteristics of engine combustion when the engine is operating with ethanol and methanol as alternative fuels. The simulations were conducted under the full-load condition for an engine operating with diesel, ethanol, and methanol. Ambient temperatures used for each test were 30, 40, and 50 °C. The results show that the in-cylinder pressure for ethanol is higher than that of methanol and diesel at different ambient temperatures, while methanol was found to yield a higher rate of heat release compared to ethanol and diesel. However, changes in ambient temperature in the inlet pipe do not affect the rate of heat release when using any fuel. It can be concluded that biofuels are excellent fuel alternatives to replace diesel in the future.